PELATIHAN DAN PENYUSUNAN RENCANA STRATEGIS (RENSTRA) SENTRUM PENGEMBANGAN PERTANIAN TERPADU (SP2T) BOLU-TORAJA UTARA - Nataniel Papalangi; Viktor Amos (Jurnal Bakti Masyarakat Indonesia, 2023)
Sentrum Pengembangan Pertanian Terpadu (SP2T) that oversees a considerable land area with an integratedagricultural development program is expected to thrive ef ectively. For this purpose, a Strategic Plan needs to beformulated. In the development of the Center for Integrated Agricultural Development (SP2T) for Socio-EconomicEmpowerment of the Archdiocese of Makassar (PSE KAMS), it is highly desirable that SP2T evolves into aself-sustaining learning institution in terms of financing, thereby reducing dependency on future proposal funding.The confidence in the outcomes of integrated agricultural processing should be substantiated, as consistentlyemphasized during the conducted training sessions. SP2T should not merely serve as a learning platform but also becapable of sustaining itself. Meanwhile, based on business analysis, this could feasibly be achieved throughagricultural and livestock enterprises. The Integrated Agricultural Development Center of Bolu (SP2T Bolu) islocated in Bolu, North Toraja Regency. This organization operates as a non-profit organization (NPO) with the aimof becoming a hub for developing local crop agriculture and managing livestock. Crop agriculture includes cropslike cof ee, fruit-bearing plants, and vegetables, while livestock includes broiler chickens, meat chickens, pigs, andgoats. In the context of agricultural development, ef orts are made to render the land productive, transforming it intoa laboratory and a model for agriculture by managing funds from KAMS and sponsors. In the context of livestock,ef orts are directed toward livestock development. ABSTRAK: Pengelolaan Sentrum Pengembangan Pertanian Terpadu (SP2T) yang mengelola lahan yang cukup luas denganprogram pengembangan pertanian terpadu diharapkan dapat berkembang dengan baik. Untuk Maksud tersebut perludisusun rencana Strategis. Dalam pengembangan Sentrum Pengembangan Pertanian Terpadu (SP2T) PemberdayaanSosial Ekonomi Keuskupan Agung Makassar (PSE KAMS), sangat diharapkan SP2T bergerak menjadi tempatpembelajaran yang mandiri dalam pembiayaan sehingga tidak tergantung pada dana proposal di kemudian hari.Keyakinan akan hasil dari pengolahan pertanian terpadu seharusnya bisa dibuktikan sebagaimana selalu diajarkandalam pelatihan – pelatihan yang dilakukan sehingga SP2T tidak menjadi lembaga yang semata jadi mediapembelajaran tapi tidak mampu menghidupi dirinya sendiri. Sementara dari analisa usaha hal ini sangat mungkindilakukan melalui usaha pertanian dan peternakan. Sentrum Pengembangan Petanian Terpadu Bolu (SP2T Bolu)terletak di Bolu, Kabupaten Toraja Utara. Lembaga ini merupakan non profit organization (NFO) yang berupayamenjadi pusat pengembangan pertanian tanaman rakyat dan mengelola peternakan. Pertanian tanaman seperti kopi,tanaman buah dan sayuran sedangkan untuk peternakan seperti ayam potong, ayam pedaging, babi dan kambing.Dalam konteks pengembangan pertanian berupaya menjadikan lahan menjadi produktif dengn menjadi salah satulaboratorium dan percontohan pertanian dengan mengelola dana dari pihak KAMS dan sponsor. Dalam kontekspeternakan berupaya melakukan pengembangan peternakan.